Investigating the Impact of Deposition Power on PVD Growth WS2 for Solar Cell Application - Sobayel K.; Nurhafiza K.; Akhtaruzzaman M.; Ayob A.; Amin N. (IEEE Computer Society, 2023)
Lime; Magnetron sputtering; Physical vapor deposition; Solar cells; Sputtering; Substrates; Sulfur compounds; Thin films; As-grown films; Deposition power; Film characteristics; Monocrystalline; Radio frequency magnetron sputtering; Soda lime glass substrate; Solar-cell applications; Ultra-thin; Tungsten compounds